Aristotle. Prior Analytics 1.1-7. Introduction and translation - Damasceno de Almeida, Wellington; R. F. Ferreira, Mateus (Revista Archai, 2023)
Translation of the initial chapters of Aristotle’s Prior Analytics into Portuguese and introduction, which addresses interpretative disagreements and translation choices.